ARN-509: a novel anti-androgen for prostate cancer treatment - Clegg, Nicola J. (2012)
Continued reliance on the androgen receptor (AR) is now understood as a core mechanism in castration-resistant prostate cancer (CRPC), the most advanced form of this disease. While established and novel AR-pathway targeting agents display clinical efficacy in metastatic CRPC, dose-limiting side effects remain problematic for all current agents. In this study, we report the discovery and development of ARN-509, a competitive AR inhibitor this is fully antagonistic to AR overexpression, a common and important feature of CRPC. ARN-509 was optimized for inhibition of AR transcriptional activity and prostate cancer cell proliferation, pharmacokinetics and in vivo efficacy. In contrast to bicalutamide, ARN-509 lacked significant agonist activity in preclinical models of CRPC. Moreover, ARN-509 lacked inducing activity for AR nuclear localization or DNA binding. In a clinically valid murine xenograft model of human CRPC, ARN-509 showed greater efficacy than MDV3100. Maximal therapeutic response in this model was achieved at 30 mg/kg/day of ARN-509, whereas the same response required 100 mg/kg/day of MDV3100 and higher steady-state plasma concentrations. Thus, ARN-509 exhibits characteristics predicting a higher therapeutic index with a greater potential to reach maximally efficacious doses in man than current AR antagonists. Our findings offer preclinical proof of principle for ARN-509 as a promising therapeutic in both castration-sensitive and castration-resistant forms of prostate cancer.